2020
DOI: 10.3389/fphar.2020.566129
|View full text |Cite
|
Sign up to set email alerts
|

Computational Prediction of Antiangiogenesis Synergistic Mechanisms of Total Saponins of Panax japonicus Against Rheumatoid Arthritis

Abstract: Objective: To investigate the anti-angiogenesis mechanisms and key targets of total saponins of Panax japonicus (TSPJ) in the treatment of rheumatoid arthritis (RA). Methods: RStudio3.6.1 software was used to obtain differentially expressed genes (DEGs) by analyzing the differences in gene expression in the synovial tissue of RA and to predict the potential targets of active compounds from TSPJ by the PharmMapper and SwissTargetPrediction databases. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Overproduction of proinflammatory cytokines contributes to immunopathology in cases of influenza virus infections (Carty et al, 2021; McElvaney et al, 2021; Pan et al, 2022; Tian et al, 2021). CHS effectively reduced the expression of TNF-α, IL-6, IL-1β, and IL-8 in both H9N2 AIV-infected A549 cells and mice, which may help prevent inflammation-induced tissue damage (Guo et al, 2020; Wang et al, 2020; Wang et al, 2021). By suppressing these key inflammatory cytokines, CHS could restrain excessive inflammation in the lungs during H9N2 AIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of proinflammatory cytokines contributes to immunopathology in cases of influenza virus infections (Carty et al, 2021; McElvaney et al, 2021; Pan et al, 2022; Tian et al, 2021). CHS effectively reduced the expression of TNF-α, IL-6, IL-1β, and IL-8 in both H9N2 AIV-infected A549 cells and mice, which may help prevent inflammation-induced tissue damage (Guo et al, 2020; Wang et al, 2020; Wang et al, 2021). By suppressing these key inflammatory cytokines, CHS could restrain excessive inflammation in the lungs during H9N2 AIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells (ECs), which provide nutrients and oxygen to the tissue, often line the vascular system, which is a heavily branched network. 16 , 59 , 61 Differentiation and proliferation of endothelial cells (ECs) occur during angiogenesis. Quiescent ECs protect blood vessels in human tissue, which are unsheathed by pericytes or mural cells when ANG-1 levels are high.…”
Section: Discussionmentioning
confidence: 99%
“…These discoveries indicated that cDHPS has the potential to be utilized in generating of functional foods or medications for the administration of RA (Shang et al, 2021). Moreover, Spirulina platensis (Ali et al, 2015), evening primrose oil (El-Sayed et al, 2014) and total Saponins of Panax japonicus (Guo et al, 2020) rely on their antiangiogenic effect to prevent the occurrence of arthritis.…”
Section: Natural Extractsmentioning
confidence: 99%